Epistimologi Islam - Siti Rapeah; Vandawa Sipahutar; Anas Habibi Ritonga (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to examine Islamic epistemology from the perspective of multidisciplinary Islamic studies by analyzing the ontological, epistemological, and axiological dimensions of knowledge in Islam. The discussion focuses on the concept of Islam in ontological studies, sources of knowledge in Islam, methods of acquiring knowledge, and the role and function of knowledge in human life. This research employs a library research method with a qualitative descriptive approach. Data were collected from relevant literature, including books, scholarly articles, and academic sources discussing Islamic epistemology. Data analysis was conducted through data reduction, data presentation, and interpretative conclusion drawing. The findings reveal that Islamic epistemology is constructed upon the integration of revelation, reason, sensory perception, and intuition as sources of knowledge. Revelation, embodied in the Qur'an and Sunnah, occupies the highest position as the ultimate source of truth, while reason, empirical experience, and intuition function as instruments for understanding and developing knowledge. The epistemological methods in Islam include the bayani (textual), burhani (rational), irfani (intuitive), empirical, and historical approaches, which complement one another in understanding reality. Furthermore, knowledge in Islam possesses a strong axiological dimension, serving as a means of drawing closer to Allah, cultivating noble character, and promoting human welfare and civilization. Therefore, Islamic epistemology offers an integrative, holistic, and value-oriented paradigm of knowledge grounded in divine principles. Keywords: Islamic epistemology, sources of knowledge, revelation, reason, axiology. Abstrak Penelitian ini bertujuan untuk mengkaji epistemologi Islam dalam perspektif studi Islam multidisipliner dengan menelaah aspek ontologis, epistemologis, dan aksiologis pengetahuan dalam Islam. Fokus kajian meliputi konsep Islam dalam perspektif ontologis, sumber-sumber pengetahuan dalam Islam, metode memperoleh pengetahuan, serta peran dan fungsi pengetahuan dalam kehidupan manusia. Penelitian ini menggunakan metode penelitian kepustakaan (library research) dengan pendekatan kualitatif-deskriptif. Data diperoleh dari berbagai literatur yang relevan, seperti buku, artikel ilmiah, dan sumber-sumber akademik yang membahas epistemologi Islam. Teknik analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan secara interpretatif. Hasil penelitian menunjukkan bahwa epistemologi Islam dibangun atas integrasi antara wahyu, akal, indera, dan intuisi sebagai sumber pengetahuan. Wahyu dalam Al-Qur'an dan Sunnah menempati posisi utama sebagai sumber kebenaran, sedangkan akal, pengalaman empiris, dan intuisi berfungsi sebagai instrumen dalam memahami dan mengembangkan pengetahuan. Metode epistemologis Islam mencakup pendekatan bayani, burhani, irfani, empiris, dan historis yang saling melengkapi dalam memahami realitas. Selain itu, pengetahuan dalam Islam memiliki dimensi aksiologis yang kuat, yaitu sebagai sarana mendekatkan diri kepada Allah SWT, membentuk akhlak mulia, serta mewujudkan kemaslahatan dan kemajuan peradaban manusia. Dengan demikian, epistemologi Islam menawarkan paradigma keilmuan yang integratif, holistik, dan berorientasi pada nilai-nilai ketuhanan. Kata kunci: epistemologi Islam, sumber pengetahuan, wahyu, akal, aksiologi.